Iris diaphragm stability during femtosecond-laser assisted cataract surgery with various preoperative non-steroidal anti-inflammatory drugs instillations - B. E. Malyugin; N. S. Anisimova; N. P. Sobolev (Офтальмохирургия, 2018)
Purpose. To compare the efficacy of two different nonsteroidal anti- the conventional phacoemulsification (CPE) was performed using the inflammatory drugs for maintenance of intraoperative mydriasis and to same preoperative instillations. Pupil diameter was registered at 5 surgical define causative factors for laser-induced miosis. steps before FLACS (first pupil diameter – I∅), before phacoemulsification Material and methods. The prospective single center investigation (II∅), after viscoinjection (III∅), at А/I of the lens cortex (IV∅), at the end included the groups I and II (35 and 30 eyes) where femtosecond laser- of the surgery (V∅). Pupil diameter was calculated in the Image J program assisted cataract surgery was carried out with bromfenac 0.09% and version 2.0. Correlation analysis was performed by uniting the groups I indomethacin 0.1% instillations. In the groups III and IV (28 and 34 eyes) and II between intraoperative parameters and pupil diameter.Results. The second degree clinical significant miosis (CSM 2) (postcapsulotomy margin of the capsule was under the iris) was detected in one patient of the group I. In the group II – 5 patients had CSM 2 on the different steps of FLACS, the smallest diameter was 4.0 mm (one case – IV∅ and one –V∅).There were correlations between II∅ with IOP measured after 15 minutes (r=-0.42, p<0.05), III∅ with IOP that was measured right after femtosecond laser procedure and 15 minutes later (r=-0.38, p<0.05; r=0.35, p<0.05 consecutively). V∅ correlated with IOP measured right after femtosecond laser step and IOP after 15 minutes (r=-0.45, p<0.001; r=0.43, p<0.001, respectively). Low negative correlations of intraoperative miosis were observed with age of the patients.Conclusion. The maintenance of intraoperative mydriasis was more stable in case of bromfenac 0.09% preoperative instillations than using indomethacin 0.1%.The patients who were older and had small pupils prior to the surgery showed a higher reduction of the pupil size. The risk factors for the intraoperative miosis were IOP spikes that occurred in the time period of 15 minutes after femtosecond laser procedure.